PENGATURAN HUKUM CALON LEGISLATIF MANTAN NARAPIDANA - Salim Fauzi Lubis; Ismail Ismail; Mina Mardiana (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2020)
Election or local election is a way of channeling the rights of every principle community, which means that the right to vote and vote is contained in his constitutional rights as citizens. In article 28 letter D of the Republic of Indonesia Republic of 1945 which reads that "every citizen has the right to have the same opportunity in government". The sound contained in the article contains the understanding that the State guarantees each of its citizens to obtain the rights to sit in government either as People's Representatives, regents, Mayors, Governors, or even become a President. The method used in this study is normative juridical legal research which uses a statutory approach. The issue raised by the author is How the Human Rights Perspective of Legislative Candidates in Organizing Elections and How Comparative Legal Arrangements for Former Legislative Candidates Examined From Law Number 7 of 2017 Concerning General Elections With Regulation of the Election Commission Number 20 of 2018 Regarding Nominating Members Regional Representative Council, Provincial Regional Representative Council, Regency / City Representative Council. In terms of the implementation of elections need to be held honestly, fairly and democratically based on the spirit of Democracy that has been carried out so far so as to create leaders and representatives of the people who side with their people. Speaking of Human Rights, everyone has the same rights before the State and applies to former corruption convicts who have or have the same political rights as other citizens guaranteed by the constitution.